2020
DOI: 10.3390/su12124867
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Impacts of Location Attributes on Residents’ Preferences and Residential Values in Compact Cities: A Case Study of Hong Kong

Abstract: In recent years, environmentally-friendly, sustainable, and compact development has become increasingly popular with governments. An extensive body of literature has focused on the influence on housing prices from an economic perspective. Although residential urban planning from the perspective of individual needs must be considered, little attention has been paid to residents’ demands in high-density and compact urban areas. In this study, we selected Hong Kong as the case and adopted a reliability interval m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…Holmlund's research in Sweden shows that for aging parents, having fewer children reduces the probability of having at least one child living nearby, which is likely to have consequences for the intensity of intergenerational contact and eldercare [44]. Bai et al studied the impact of Location Attributes on Residents' Preferences and Residential Values in Hong Kong, and they found that little attention has been paid to residents' demands in high-density and compact urban areas [45]. Kim's research on Japan and Korea found that determinants of living arrangements of the elderly parents and married children are rough for not only the needs of elderly parents but also married children [46].…”
Section: Discussionmentioning
confidence: 99%
“…Holmlund's research in Sweden shows that for aging parents, having fewer children reduces the probability of having at least one child living nearby, which is likely to have consequences for the intensity of intergenerational contact and eldercare [44]. Bai et al studied the impact of Location Attributes on Residents' Preferences and Residential Values in Hong Kong, and they found that little attention has been paid to residents' demands in high-density and compact urban areas [45]. Kim's research on Japan and Korea found that determinants of living arrangements of the elderly parents and married children are rough for not only the needs of elderly parents but also married children [46].…”
Section: Discussionmentioning
confidence: 99%
“…Pairwise comparison can easily cause confusion, especially when there are many indicators. RIM asks respondents to provide an interval range evaluation for each index, which can reduce arbitrariness and confusion [43,44]. Compared with other MCDA methods (such as AHP), this method is clearer and easier to use, and is more suitable for assessing participants' views on a large number of indicators [45].…”
Section: Methodsmentioning
confidence: 99%
“…A survey for this distance determination from a study was done by the authors of [12]. Some studies, such as Tsai et al [10], Lai et al [42], Wu et al [40], Xue et al [43], and Bai et al [44] use the acceptable walking distance. However, the determination of the impact radius from the above methods lacks an empirical basis.…”
Section: Determination Of the Impact Radius For Open Space With And Without Adjacent Nimby Or Yimby Facilities And Other Surrounding Charmentioning
confidence: 99%